P11.10 The IFNγ pathway mediates brain metastasis formation of breast cancer. (6th September 2019) - Pedrosa, R; Kros, J M; Schrijver, B; Marques, R; Leenen, P; Dik, W; van Eijck, C; Mustafa, D
Abstract: BACKGROUND: In previous work we showed the prominence of the T-cell response in the formation of brain metastases of primary ER negative breast cancers (Mustafa et al, Acta Neuropathol 2018). We also showed that breast cancer cells co-cultured with stimulated T lymphocytes overexpress Guanylate-binding protein 1 (GBP1) accompanying increased trespassing ability through an in vitro blood-brain barrier (BBB) model. In addition, we demonstrated a predilection for metastasizing to brain of breast cancer cells that were co-cultured with activated T cells in a mouse model. We now scrutinize the importance of the IFNγ pathway for tresspassing of the tumor cells through the BBB following T cell contact. MATERIAL AND METHODS: Anti-hIFN-γ-IgA antibodies were used to neutralize the IFNγ effects on the tumor cells. The effects on the tumor cells is only due to native IFNγ produced by activated T cells, not by recombinant IFNγ. Since the IFNγ expression itself enhances its expression by the T cells, we blocked IFNγ receptors prior to adding CD3+ T cell conditioned media to the breast cancer cells. The receptor blocking was achieved by antibodies to the IFNγα and IFNγβ subunits. Activation of the STAT1 pathway was monitored by GBP1 expression. For functional read-out the in vitro BBB model was used. RESULTS: The presence of T-lymphocyte-secreted IFNγ in the primary breast cancer microenvironment activates the STAT1-dependent IFNγ pathway in breast cancer cells, endowing them with an increased ability to trespass the in vitro BBB. Moreover, direct inhibition of soluble IFNγ, or blocking of the IFNγ-specific receptor in breast cancer cells significantly decreases their ability to cross the BBB. CONCLUSION: The results illustrate the specific action of T lymphocytes in the formation of cerebral metastasis involves the IFNγ signaling pathway as one of the crucial entangled pathways Subsequent studies should aim at the interference with the IFNγ pathway to develop preventive strategies against the formation of cerebral metastases of breast cancer.